2019
DOI: 10.1152/ajpendo.00215.2019
|View full text |Cite
|
Sign up to set email alerts
|

CD44 contributes to hyaluronan-mediated insulin resistance in skeletal muscle of high-fat-fed C57BL/6 mice

Abstract: Extracellular matrix hyaluronan is increased in skeletal muscle of high-fat-fed insulin-resistant mice, and reduction of hyaluronan by PEGPH20 hyaluronidase ameliorates diet-induced insulin resistance (IR). CD44, the main hyaluronan receptor, is positively correlated with type 2 diabetes. This study determines the role of CD44 in skeletal muscle IR. Global CD44-deficient ( cd44−/−) mice and wild-type littermates ( cd44+/+) were fed a chow diet or 60% high-fat diet for 16 wk. High-fat-fed cd44−/− mice were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…CD44 acts as both a receptor for hyaluronan and osteopontin, of which both molecules are associated with the pathogenesis of DM. For example, hyaluronan promotes muscle insulin resistance (38). There is also a critical role for osteopontin in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 acts as both a receptor for hyaluronan and osteopontin, of which both molecules are associated with the pathogenesis of DM. For example, hyaluronan promotes muscle insulin resistance (38). There is also a critical role for osteopontin in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM is composed of the interstitial matrix (e.g., fibrillar collagens, fibronectin, hyaluronan) and the basement membrane (e.g., collagen IV and laminin), which provide the structural support for tissues and are required for cell adhesion and migration during growth, differentiation, morphogenesis and wound healing [3]. Increased deposition of various ECM components (e.g., collagens, hyaluronan and osteopontin) and their binding to the ECM receptors (e.g., integrins and CD44) have been linked to the development of obesity-associated insulin resistance in skeletal muscle [4][5][6], adipose tissue [7,8] and the liver [9].…”
Section: Introductionmentioning
confidence: 99%
“…Collagens are the most abundant components of the ECM, consisting of three α-helical chains made of the repetitious amino acid sequence glycine-X-Y, where X and Y are frequently proline or hydroxyproline. It was previously shown that collagen isoforms I (1), III (3), IV (4), V (5), VI (6) and XVIII (18) were increased in insulin-resistant tissues [1,14]. Collagen XXIV (24) was discovered as a new member of the fibril-forming family of collagen molecules and has been demonstrated to be crucial for osteoblastic differentiation and mineralisation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is still a lack of direct evidence, the current outcomes have suggested the possible roles of prioritized genes in CVD progression. The prioritized genes such as RSPO3, TUFM, SBF2, TBCE, PIEZO1, CD44, ABCB10, C1S, HDAC7, and ATF-1 have also been associated with the potential causative risk factors identified by our MR analysis [63][64][65][66][67][68][69][70][71][72] . These genes linking risk factors to CVD should be targets in future studies of the molecular basis of possible genetic contributions to CVD.…”
Section: Discussionmentioning
confidence: 99%